An Analytical Study of History Teacher Competencies for the Transmission of Cultural and Artistic Values of Architectural Heritage: A Case Study of Lintels in Angkorian Stone Sanctuaries in Thailand - Hongcharoen, Thawisak; Bangchuad, Doungkamol; Triwaranyu, Charinee (Rajapark Journal, 2026)
The purposes of this research were to study the learning goals of history students that affect the transmission of lintel values, and to analyze the competencies of history teachers in transmitting the values of ancient architectural art: a case study of lintel reliefs from Angkor-period stone sanctuaries in Thailand. The key informants comprised 210 students and 75 teachers, selected through quota sampling. The research instrument was a questionnaire validated by the Index of Item-Objective Congruence (IOC). Data were analyzed using the arithmetic mean ( ), standard deviation (S.D.), and the Modified Priority Needs Index (PNImodified). The results of the research were as follows: 1) The learning goals of students in history that affect the transmission of lintel values had an overall mean at a high level ( = 4.106, S.D. = 0.676). When considering each aspect, it was found that the attribute aspect had the highest mean at a high level ( = 4.259, S.D. = 0.748), and the lowest was the skill aspect, which still had a mean at a high level ( 3.971, S.D. = 0.764). 2) The analysis of history teacher competencies for transmitting the values of ancient architectural art: a case study of lintel reliefs of Angkor-period stone sanctuaries in Thailand showed that the overall Modified Priority Needs Index (PNI(Modified) = 0.612). When considering each aspect, it was found that the development of professional networks had the highest priority needs index (PNI(Modified) = 0.698), followed by instructional design in history (PNI(Modified) = 0.684), followed by knowledge of curriculum and historical content (PNI(Modified) = 0.655), and the lowest priority needs index was historical consciousness (PNI(Modified) = 0.516).